UTILIZING THE POTENTIAL OF TECHNOLOGY TO IMPROVE THE QUALITY OF LEARNING IN MADRASAH - Edi Ansyah (International Journal of Teaching and Learning, 2024)
In today's digital age, education technology has become an important element in learning transformation in various educational institutions, including the madrasah. The research aims to explore a variety of technology models that can be integrated into the learning system in the madrasah, in order to improve the quality and effectiveness of learning. Through literature analysis, the study identified three key technologies that have great potential in improving learning in the madrasah: Learning Management Systems (LMS), game-based educational technologies, and augmented reality (AR) technologies. The research shows that LMS integration facilitates more organized and efficient learning management, enabling educators to provide learning materials digitally, carry out assessments, and communicate with students in real-time. Game-based education has been found to be effective in increasing student motivation and engagement, presenting learning materials in an interesting and interactive format. Meanwhile, the application of AR technology offers an immersive learning experience, enabling students to gain in-depth understanding through the visualization of learning concepts. The results suggest that the use of technology in learning in the madrasah not only opens up access to innovative and varied learning resources, but also integrates Islamic values into the learning process more effectively. However, the success of this technology integration depends on several key factors, including adequate training for educators, the availability of adequate technological infrastructure, as well as the choice of technology that suits the needs and contexts of the madrasah.